Teleconnection between Australian winter temperature and Indian summer monsoon rainfall - Lee, Soo-Ying (2013)
The large-scale circulation over the Indian Ocean during the boreal summer raises the question of whether atmospheric conditions in Australia could influence conditions over the Indian subcontinent, despite the long passage of air over the Indian Ocean. Using a combination of reanalysis, satellite and in situ data, we argue that unusually low temperature over inland Australia during austral winter can enhance evaporation rate over the eastern tropical Indian Ocean, and hence enhance rainfall over western India after 10–18 days. Since extreme winter temperature in Australia is often associated with cold-air outbreaks, the above mechanism can be an example of how southern hemispheric mid-latitude weather can influence northern hemispheric monsoon rainfall.